Strategi Transformasi Digital Pengembangan Bisnis di PT Gemilang Indonesia Sukses Mulia - Andi Irman Patiroi; Nimmi Zulbainarni; Irman Hermadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Digital transformation has become an urgent need for organizations that want to remain relevant and competitive in today's digital era. However, in the face of the wide choice of business development strategies available, decision making can become complicated. Therefore, this thesis proposes a systematic and structured approach using the Analytical Hierarchy Process (AHP) method to identify and evaluate the most appropriate business development strategies in the context of digital transformation. This research integrates qualitative and quantitative approaches by utilizing a comprehensive literature review and in-depth AHP analysis. Thus, this thesis not only understands the key factors influencing the success of digital transformation, but also offers a clear framework for measuring and prioritizing alternative strategies. Through the AHP application, various criteria and sub-criteria relevant to digital transformation are identified and ranked according to their importance. The results of this evaluation then provide more focused guidance in selecting business development strategies that can optimize the use of digital technology, minimize risks and achieve long-term business goals. Thus, this thesis not only makes a theoretical contribution to the understanding of digital transformation, but also makes a practical contribution by providing a methodology that can be applied by business leaders and decision makers in guiding business development strategies in this digital era.